Mind the wellness - William, Andrew (Nanyang Technological University, 2022)
Mind the Wellness is a communication campaign aimed to encourage youths aged 21 to 35 years old to take care of their mental health by engaging in mental wellness activities. According to the Ministry of Health, there was a spike in mental health conditions, especially amongst youths aged 18-29 from 16.5% in 2017 to 21.5% in 2020. IMH’s study in 2016 also reported a higher occurrence of mental disorder issues between the ages of 18 to 34. In response to the rising cases of mental health issues in Singapore, many initiatives revolving around mental health were executed. However, most initiatives focused on cure rather than prevention. Coupled with the existing stigma revolving around the topic, youths tend to shun away from seeking help in the face of adversity, putting a further strain on the mental health landscape. This calls for an urgent intervention to equip youths with de-stressors and coping techniques. Based on the multiple regression model, attitude and perceived behavioural control were found to be the two statistically significant constructs of the Theory of Planned Behaviour model. Hence, Mind The Wellness sought to expose our TA to a series of fun and enjoyable workshops, whilst providing them the necessary knowledge pertaining to mental wellness. Additionally, constant reminders were also introduced to encourage our TA to take care of their mental wellness on a regular basis, not only during pressing times, to inculcate the habit of constantly maintaining their mental wellness. Upon conducting post-campaign evaluation, Mind the Wellness recorded a notable increase across all constructs, exceeding most predetermined impact objectives, with the significant increase in perceived behavioural control taking the centre stage. Furthermore, the primary research findings will also be shared with the Ministry of Culture, Community & Youth (MCCY) to be used as a guidance for future campaign programming.